2019
DOI: 10.1038/s41443-019-0136-9
|View full text |Cite
|
Sign up to set email alerts
|

Intratunical injection of autologous adipose stromal vascular fraction reduces collagen III expression in a rat model of chronic penile fibrosis

Abstract: Previous studies have shown that the injection of adipose stem cells and stromal vascular fraction(SVF) into the tunica albuginea (TA) during the inflammatory phase in a rat model of Peyronie's disease(PD) prevented the development of TA fibrosis. Our aim was to investigate whether local injection of SVF can reduce established fibrosis in a rat model of chronic phase of PD. Eighteen-male 12-wk-old Sprague-Dawley rats were divided in three equal groups: sham, PD without treatment (PD) and PD treated with SVF(PD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
5
0
1
Order By: Relevance
“…Studies showed that both allogeneic and xenogenic ADSCs injection could decrease TGF-β1 induced urethral fibrosis with the downregulation of collagen I and collagen III 6 , 23 . Adipose tissue derived SVF, consisting of heterogeneous cell populations including ADSCs, is reported to be capable of preventing fibrotic changes of penile fibrosis in acute and chronic phase of Peyronie’s disease 9 , 24 . We previously found that local injection of SVF cells contributed to the attenuation of ischemia–reperfusion injury induced renal fibrosis 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that both allogeneic and xenogenic ADSCs injection could decrease TGF-β1 induced urethral fibrosis with the downregulation of collagen I and collagen III 6 , 23 . Adipose tissue derived SVF, consisting of heterogeneous cell populations including ADSCs, is reported to be capable of preventing fibrotic changes of penile fibrosis in acute and chronic phase of Peyronie’s disease 9 , 24 . We previously found that local injection of SVF cells contributed to the attenuation of ischemia–reperfusion injury induced renal fibrosis 8 .…”
Section: Discussionmentioning
confidence: 99%
“… 36 Few articles in the sexual medicine field have reported the use of the ARRIVE checklist. 38 , 39 , 40 , 41 This concept is very important because similar to humans, several mammals display —in aging or because of various diseases—signs of ED and alterations of important regulatory pathways of erection. 24 The lack of crucial information can prevent the correct evaluation of the final results obtained.…”
Section: General Concepts Of Translational Research—the Animal Researmentioning
confidence: 99%
“…However, it is also associated with a high variability of the SVF’s therapeutic potential among individuals, making it more complicated to standardize SVF-based treatments[ 116 ]. The use of SVF as treatment of urogenital disorders has been widely investigated in recent years in particular for preclinical studies for erectile disfunction and for Peyronie’s disease[ 117 - 120 ]. Moreover, a small number of early clinical studies using injected SVF for urogenital system related pathologies, like urinary incontinence, erectile disfunction, and Peyronie’s disease, have been performed in the last years[ 121 - 123 ].…”
Section: Towards Clinical Applicationsmentioning
confidence: 99%